2020
DOI: 10.1021/acsomega.0c03408
|View full text |Cite
|
Sign up to set email alerts
|

Application, Synthesis, and Characterization of Cationic Galactomannan from Ruderal Species as a Wet Strength Additive and Flocculating Agent

Abstract: There has been a cumulative interest across the globe in substituting the synthetic materials with sustainable, economical, and biobased green alternatives for utilization in diverse industrial applications. Galactomannans are among the most important sustainable, biodegradable macromolecules abundantly produced by plants, which can be exploited for a range of end-use applications. Functionalization of the galactomannans may improve the physicochemical properties for diverse industrial applications. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The 1 H‐NMR spectrum of guar and derivatized guar gum showed characteristic chemical shifts clustered between δ 3.2 ppm to 4 ppm for ring protons of mannose/galactose units simultaneously. The 1 H‐NMR spectrum of quaternized guar gum indicated the presence of an additional signal at δ 3.06 ppm (as a sharp singlet) corresponding to the methyl protons of quaternary ammonium [−N + (CH 3 ) 3 ] groups, thereby confirming the incorporation of quaternizing moiety as trimethyl ammonium group in the galactomannan chain [31,43,44] …”
Section: Nmr Characterizationmentioning
confidence: 95%
“…The 1 H‐NMR spectrum of guar and derivatized guar gum showed characteristic chemical shifts clustered between δ 3.2 ppm to 4 ppm for ring protons of mannose/galactose units simultaneously. The 1 H‐NMR spectrum of quaternized guar gum indicated the presence of an additional signal at δ 3.06 ppm (as a sharp singlet) corresponding to the methyl protons of quaternary ammonium [−N + (CH 3 ) 3 ] groups, thereby confirming the incorporation of quaternizing moiety as trimethyl ammonium group in the galactomannan chain [31,43,44] …”
Section: Nmr Characterizationmentioning
confidence: 95%
“…Reviews and chemical methods have been reported in the past to increase the functional behaviour of hydroxyl groups present in the polysaccharides. These methods have their own limitations for particular industrial aspects and are used for diverse industrial applications [83][84][85][86][87][88][89][90][91][92][93][94]. Mercerization, benzoylation, acrylation, acrylonitrile grafting, permanganate treatment, peroxide treatment, and isocyanate treatment, bleaching, acetylation, silane and peroxide treatments, etherifications viz.…”
Section: Chemical Modification Of Fibresmentioning
confidence: 99%
“…12 Consequently, researchers are searching for wet-strength agents with comparable properties to PAE that have less environmental impact and pose fewer health risks. 13 In addition to wet-strength chemicals themselves, internal sizing agents are also utilized to modify the fiber surface. Some of these agents allow for control of the liquid permeability, and dry-strength agents can be added to improve paper strength.…”
Section: High-performance Wet-end Chemicals Inmentioning
confidence: 99%
“…Moreover, the resulting paper becomes nonbiodegradable and nonrecyclable when too much PAE is used . Consequently, researchers are searching for wet-strength agents with comparable properties to PAE that have less environmental impact and pose fewer health risks …”
Section: High-performance Wet-end Chemicals In the Papermakingmentioning
confidence: 99%